The hedaya on gifts and wills : exhaustive commentry [sic] - Chaudhary, Abdul Wahid (Pakistan Law Book Centre : can be had from, Lahore Law Times Publications, 1979)
Gifts and wills according to the Hanafi school of Islamic law.